Evaluate serum proteome in women with obsessive-compulsive disorder/bipolar compared with pure OCD subjects as well as healthy controls - rezaei-tavirani, mostafa; Tahery, noorollah; Zamanian Azodi, Mona; Hamedieh, Mostafa; Rostami Nejad, Mohammad; Mahmoodi, Nahid (Iranian Journal of Child Neurology, 2023)
Objectives The present study aimed to evaluate the serum proteome of women with obsessive-compulsive disorder (OCD)/bipolar disorder (BP) compared to pure OCD subjects and healthy controls. Materials & Methods Serum proteome of women with OCD/BP, pure OCD individuals, and healthy controls were subjected to 2DE-based proteomics accompanied with MALDI-TOF-TOF mass spectrometry. Further evaluation of the identified protein spots with the significance of p<0.05 and fold≥1.5 was done by applying protein interaction mapping via Cytoscape v.5.3.1 and its plugins. Results The results indicate that vitamin D binding protein (GC) and haptoglobin spots (HP) significantly changed expression in OCD and OCD/BP with different expression patterns. These identified spots may contribute to OCD/BP and act as differentially recognized biomarkers comparing pure OCD and OCD/BP. Conclusion The Findings imply that these proteins in the serum of the patients could be potential distinguishable biomarkers in clinical usage after related validation experiments. Therefore, this study provides a preliminary evaluation to understand OCD/BP proteome behavior better.